Sensor Data Handling by Personal Computer - Woldehanna, Frehiwot (Zede Journal of Ethiopian Engineers and Architects, 2023)
An eight channel sensor data acquisition and processing system has been built and tested. The hardware, built on an IBM PC AT interface board, contains a multiplexed AID converter and board memory. Fully menu-driven software, written in C language, selects the necessary hardware parameters and initiates a DMA transfer of the sampled data and provides an option for selection of processing algorithm. Sensor calibration and correlation computation algorithms have been incorporated as part of processing algorithms.